A variational principle for complex boundary value problems - Adnan Atef Hajj (International Journal of Mathematics and Mathematical Sciences)
This paper provides a variational formalism for boundary value problems which arise in certain feilds of research such as that of electricity, where the associated boundary conditions contain complex periodic conditions. A functional is provided which embodies the boundary conditions of the problem and hence the expansion (trial) functions need not satisfy any of them.